Tumor-Educated Platelets Facilitate Thrombus Formation Through Migration - Liu, Zheming; Wang, Jing; Liao, Fuben; Song, Qibin; Yao, Yi (Frontiers in Oncology, 2022)
Platelets are small anucleate cells that circulate in the blood and form thrombi. Tumor-educated platelets are the platelets derived from cancer patients. Although many have reported that tumor-educated platelets are associated with cancer-associated thrombosis, their function in this process is poorly understood. Here we first collect the clinical data from 100 different cancer patients, showing that cancer patients are in a hypercoagulable state. Our experiment shows that tumor-educated platelets from melanoma burdened mice models can migrate faster and longer, forming more clots (thrombus). However, the plasma from tumor mice can inhibit platelets migration. RNA sequence profile of tumor-educated platelets shows that many genes associated with cell migration and cell skeleton expressed significantly higher. Our research offers a new insight into the tumor-educated platelets to better understand the thrombus formation.